Garden Shelterbelts: Protecting Yesterday's Gardens Tomorrow - Lyte, Benedict; Warren, Jolin; Haenraets, Jan; Mitchell, David (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2008)
Shelterbelts in gardens, as their name implies, provide crucial protection from strong winds for the less well-adapted species growing behind them. Several of the historic gardens on the west coast of Scotland rely on them in order to cultivate the range of plants that they do. Many of these windbreak plantings were established over 150 years ago and the plants in them are ageing. The National Trust for Scotland held a seminar to discuss this problem and the experiences of a number of gardens, and the lessons learnt are described. New computer-based technology developed by the Forestry Commission is also discussed.